Anesthesia [videorecording (DVD)] - Nelson, Tim Blake; Nelson, Tim Blake; Nelson, Tim Blake; Waterston, Sam; Stewart, Kristen, 1990-; Stoll, Corey, 1976- (IFC Films, 2016)
While on his way home one evening, Walter Zarrow, a popular Columbia University philosophy professor, is violently attacked on the street. Flashing back one week to the beginning of a domino effect of events that led up to this seemingly senseless assault, the film traces hidden connections between an apparently disparate group of people.